ESTUDIO SEROLÓGICO DE DURINA Y MUERMO EQUINO - Rivera G., Hermelinda (2002)
Durine and Glanders are cronic and progressive infectious diseases of horses, donkeys and mules, and human beings in case of glanders. These diseases are caused by a parasite, Trypanosoma equiperdum (T. equiperdum) and a bacteria Burkholderia mallei (B. mallei), respectively. In Peru there are no information about the clinical and serological evidence of durine and glanders. The objective of this study was to detect antibodies against T. equiperdum and B. mallei in serum samples from horses (n=505) of normal appearance, and from different areas of Peru but mainly from Lima by using the complement fixation test. No antibodies against T. equiperdum and B. mallei were detected in the serum samples tested. These results suggest that both diseases are absent or the prevalence are below 1% in the studied Peruvian horses .